2021
DOI: 10.1111/apt.16479
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: efficacy of escalated maintenance anti‐tumour necrosis factor therapy in Crohn's disease

Abstract: Summary Background Loss of response to anti‐TNF agents is a common clinical problem. Dose escalation may be effective for reestablishing clinical response in Crohn's disease (CD). Aims To perform a systematic review assessing the efficacy of escalated maintenance anti‐TNF therapy in CD. Methods EMBASE, MEDLINE, Web of Science, and CENTRAL databases were searched for English language publications through to April 25, 2021. Full‐text articles evaluating escalated maintenance treatment (infliximab or adalimumab) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 89 publications
(516 reference statements)
0
11
0
Order By: Relevance
“…Delphi participants agreed that in the case of loss of response to anti-TNF therapy due to immunogenicity, assessing whether immunogenicity was preventable appears to be vital in order to improve CD management. In patients with secondary loss of response due to immunogenicity, a great variability in the rates of clinical response (33–100%) and remission (15–83%) was found upon empirical anti-TNF dose intensification 73. Small observational studies have reported reductions in antibody levels and increases in drug trough levels resulting in clinical responses upon adding an IMM drug 26 74–79.…”
Section: Resultsmentioning
confidence: 99%
“…Delphi participants agreed that in the case of loss of response to anti-TNF therapy due to immunogenicity, assessing whether immunogenicity was preventable appears to be vital in order to improve CD management. In patients with secondary loss of response due to immunogenicity, a great variability in the rates of clinical response (33–100%) and remission (15–83%) was found upon empirical anti-TNF dose intensification 73. Small observational studies have reported reductions in antibody levels and increases in drug trough levels resulting in clinical responses upon adding an IMM drug 26 74–79.…”
Section: Resultsmentioning
confidence: 99%
“…In iximab and adalimumab have been approved in mainland China for the treatment of CD, the recommended maintenance dose for adalimumab is 40 mg every other week (14). However, some CD patients do not achieve a clinical response to the standard dose of adalimumab, with the primary and secondary non-response rates for 10-30% and 23-46%, respectively (15). The results of our study suggest that both standard and high doses of adalimumab are effective in inducing clinical remission in patients with Crohn's disease, with no signi cant different in clinical remission rates (78.0% vs 73.8% P = 0.674) or time to treatment failure (HR0.6,95%CI [0.27,1.36], P = 0.225) between the two regimens in in iximab-naïve CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are difficult to explain. The clinical response and clinical remission rates were, respectively, 34% to 90% and 26% to 81% after dose escalation of IFX and 33% to 100% and 15% to 83% after dose escalation of ADA [ 23 ]. In patients with secondary LOR to ADA, administering ADA at an escalated dose of 80 mg every 2 weeks or at a dose of 40 mg every week was effective, but 56.8% of patients experienced tertiary LOR [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical response and clinical remission rates were, respectively, 34% to 90% and 26% to 81% after dose escalation of IFX and 33% to 100% and 15% to 83% after dose escalation of ADA. 23 In patients with secondary LOR to ADA, administering ADA at an escalated dose of 80 mg every 2 weeks or at a dose of 40 mg every week was effective, but 56.8% of patients experienced tertiary LOR. 24 In recent years, the importance of the treat-to-target strategy www.irjournal.org has been emphasized to improve the long-term prognosis of inflammatory bowel disease.…”
mentioning
confidence: 97%